(untitled) (Revista Innova Educación, 2024)
The development of assertiveness and empathy in the school environment contributes to creating a positive atmosphere, preventing bullying, promoting socio-emotional development, and improving academic performance. Therefore, the objective of this study is to analyze the level of assertiveness and empathy in aggressors and victims in school coexistence in primary education in an urban municipality in the province of Granada (Spain), with the aim of proposing an innovative teaching practice in response to this coexistence environment and improving the quality of education. The approach was quantitative, with a descriptive design. The sample consisted of 47 participants from the 6th grade, aged between 11 and 13 years (M = 11.43; SD = 0.50), to whom the Assertive Behavior Scale for Children (CABS) and the Interpersonal Reactivity Index were applied to measure assertiveness and empathy, respectively. The results revealed that students who act as aggressors or consider themselves victims show lower levels in both competencies (3.90% aggressors, 30.30% victims, 69.70% non-victims). Therefore, assertiveness and empathy are not only independent skills but are interrelated and mutually reinforcing. Thus, to reduce aggressive behaviors and situations of victimization, it is essential to promote both assertiveness and empathy. It is concluded that by developing these skills, more effective and respectful communication is promoted, which can decrease conflicts and improve school coexistence.